Spectroscopic investigations of Nd3+doped gadolinium calcium silica borate glasses for the NIR emission at 1059ï¿½nm - C. R. Kesavulu (2018)
ï¿½ 2016 Elsevier B.V. The Nd 3+ -doped gadolinium calcium silica borate (BSGdCaNd) glasses of composition (55-x) B 2 O 3 - 10 SiO 2 - 25 Gd 2 O 3 -10 CaO -x Nd 2 O 3 , where xï¿½=ï¿½0.0, 0.05, 0.5, 1.0, 1.5, 2.0 and 2.5ï¿½mol %, have been prepared by conventional melt quenching technique and are characterized through structural, thermal, absorption, emission and decay time measurements. Based on the Judd-Ofelt intensity parameters and radiative properties were determined from the absorption spectrum. The emission spectra recorded for BSGdCaNd glasses gives three emission transitions 4 F 3/2 ï¿½→ï¿½ 4 I 9/2 (903ï¿½nm), 4 F 3/2 ï¿½→ï¿½ 4 I 11/2 (1059ï¿½nm) and 4 F 3/2 ï¿½→ï¿½ 4 I 13/2 (1334ï¿½nm) for which effective bandwidths (Δλ eff ) and stimulated emission cross-section (σ(λp)) are evaluated. Branching ratios (β R ) measured for BSGdCaNd0.5 glass show that 4 F 3/2 ï¿½→ï¿½ 4 I 11/2 transition is quite suitable for lasing applications. The intensity of emission spectra increases with increase in the concentration of Nd 3+ ion up to 1.0ï¿½mol% and beyond that concentration, quenching is observed. The decay from 4 F 3/2 level is found to be non-exponential nature for concentrations of Nd 3+ ions. The non-exponential curve has been fitted to the Inokuti-Hirayama model to understand the nature of energy transfer process. Hence, the high emission cross-section (1.39ï¿½× 10 −20 ï¿½cm 2 ), branching ratio (0.58) and long lifetime (342ï¿½μs) indicate that the BSGdCaNd0.5 glass system could be considered as a good candidate for strong NIR lasers at 1059ï¿½nm.